2022
DOI: 10.31579/2578-8965/109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Caffeine and Vitamin E Usage on Fetus

Abstract: The use of maternal caffeine has an important effect on the development of the fetus. We investigated the mechanism of oxidative damage induced by caffeine and the efficacy of vitamin E. Pregnant rats of Wistar-albino genus were used. Following groups of animals were defined: control, sham, caffeine (50 mg/kg), caffeine + vitamin E, vitamin E (60 mg/kg) all invasive applications were repeated daily for 20 days. Tumor necrosis factor alpha (TNF-α), interleukin 1β(IL-1β), interleukin 6 (IL-6) levels were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…CAF (1,3,7-trimethylxanthine) is an alkaloid belonging to the group of methylxanthines, which is consumed almost daily and has many effects on the CNS. Today, numerous studies suggest the negative effects of excessive consumption of the CAF during pregnancy on the fetus [12]. The main reason for this is that the CAF can easily pass through the placenta and cytochrome P450 A2, which is the necessary enzyme in CAF metabolism, is not found in the fetus [1,2,4,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAF (1,3,7-trimethylxanthine) is an alkaloid belonging to the group of methylxanthines, which is consumed almost daily and has many effects on the CNS. Today, numerous studies suggest the negative effects of excessive consumption of the CAF during pregnancy on the fetus [12]. The main reason for this is that the CAF can easily pass through the placenta and cytochrome P450 A2, which is the necessary enzyme in CAF metabolism, is not found in the fetus [1,2,4,11].…”
Section: Discussionmentioning
confidence: 99%
“…CAF can easily cross both the blood-brain barrier and the placental barrier [1,2,4,11,12]. Studies have reported that caffeine mixed with the drinking water of pregnant animals passes to the fetus [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely consumed by pregnant women, and the potential effects of CAF intake in pregnant women on the developing fetus have been investigated in animals and humans in recent years (Rivkees & Wendler, 2017; Wierzejska et al, 2019). Studies have reported that CAF and its metabolites can easily cross both the blood–brain barrier (BBB) and the placental barrier during pregnancy, resulting in accumulation in the fetal brain (Concas et al, 2000; Kou et al, 2017; Mioranzza et al, 2014; Papadopoulou et al, 2018; Peacock et al, 2018; Yılmaz et al, 2022; Zhan et al, 2022). As a result of decreased cytochrome P450 enzyme activity in liver of fetus, half‐life of CAF is longer in fetus between the first and third trimesters, resulting in increased fetal exposure (Papadopoulou et al, 2018; Peacock et al, 2018; Wierzejska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%